Analysis of Influence of Structural Parameters of Regenerative Cooling Channel of Scramjet. (September 2020) - Gao, Feng; Zhang, Qian; Xiao, Hongyu; Chen, Fengli; Xia, Xuefeng
Abstract: In this paper, a three-dimensional modeling analysis of regenerative cooling channels of scramjet engines is carried out, and the cooling channel structure parameters such as inner wall thickness, fin thickness, channel aspect ratio, cross-sectional area and number of channels are used to cool the regenerative cooling. The conclusion is as follows: the thinner inner wall thickness corresponds to a lower wall temperature, while the heat flux density is larger, and the kerosene temperature and pressure change little; the thin fins correspond to the higher wall temperature and oil temperature, but the kerosene is in the cooling channel. The pressure loss is smaller, and the thicker fins have a lower maximum wall temperature and maximum oil temperature, but a larger pressure loss; the greater the aspect ratio, the better the cooling effect of the channel, and the wall temperature and oil temperature are relatively low, but also It is not possible to choose a cooling channel with an aspect ratio that is too large. This is because after the aspect ratio is greater than 1, the pressure loss in the channel increases as the aspect ratio increases; reducing the channel cross-sectional area can increase the flow rate, thereby increasing convection The heat transfer coefficient makes the maximum wall temperature and oil temperature lower, but the kerosene with a too small channel area has a larger flow resistance in the channel, and the effective heat exchange area also becomes smaller; an increase in the number of channels can make the transfer Heat is strengthened, and cooling channels can be arranged more when the temperature of the material permits to give full play to the kerosene heat sink and fin effect to enhance the cooling effect.